GOODS-HERSCHEL AND CANDELS: THE MORPHOLOGIES OF ULTRALUMINOUS INFRARED GALAXIES AT z similar to 2 - Kartaltepe, J; Dickinson, M; Alexander, D; Bell, E; Dahlen, T; Elbaz, D; Faber, S; Lotz, J; McIntosh, D; Wiklind, T; Altieri, B; Aussel, H; et al. (2012)
Using deep 100 and 160 μm observations in GOODS-South from GOODS-Herschel, combined with high-resolution HST/WFC3 near-infrared imaging from CANDELS, we present the first detailed morphological analysis of a complete, far-infrared (FIR) selected sample of 52 ultraluminous infrared galaxies (ULIRGs; LIR > 1012 L⊙) at z ∼ 2. We also make use of a comparison sample of galaxies with lower IR luminosities but with the same redshift and H-band magnitude distribution. Our visual classifications of these two samples indicate that the fractions of objects with disk and spheroid morphologies are roughly the same but that there are significantly more mergers, interactions, and irregular galaxies among the ULIRGs (72+5 -7% versus 32 ± 3%). The combination of disk and irregular/interacting morphologies suggests that early-stage interactions, minor mergers, and disk instabilities could play an important role in ULIRGs at z ∼ 2. We compare these fractions with those of a z ∼ 1 sample selected from GOODS-H and COSMOS across a wide luminosity range and find that the fraction of disks decreases systematically with LIR while the fraction of mergers and interactions increases, as has been observed locally. At comparable luminosities, the fraction of ULIRGs with various morphological classifications is similar at z ∼ 2 and z ∼ 1, though there are slightly fewer mergers and slightly more disks at higher redshift. We investigate the position of the z ∼ 2 ULIRGs, along with 70 z ∼ 2 LIRGs, on the specific star formation rate versus redshift plane, and find 52 systems to be starbursts (i.e., they lie more than a factor of three above the main-sequence relation). We find that many of these systems are clear interactions and mergers (∼50%) compared to only 24% of systems on the main sequence relation. If irregular disks are included as potential minor mergers, then we find that up to ∼73% of starbursts are involved in a merger or interaction at some level. Although the final coalescence of a major merger may not be required for the high luminosities of ULIRGs at z ∼ 2 as is the case locally, the large fraction (50%-73%) of interactions at all stages and potential minor mergers suggests that these processes contribute significantly to the high star formation rates of ULIRGs at z ∼ 2. © 2012. The American Astronomical Society. All rights reserved.